Signifikansi ekspresi nilai simbol budaya peciren bebadungan pada desain fasad bangunan publik di Bali - I Kadek Pranajaya; Made Mariada Rijasa; Ni Made Emmi Nutrisia Dewi (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
There is a need to preserve areas with distinct identities by utilizing several local architectural potentials to develop their appearances. One example of this is in the Denpasar and Badung regions of Bali, where the use of peciren bebadungan ornaments is currently being applied to shape their respective identities. The peciren bebadungan is an expression of brick tectonics with strong, hard, and simple characteristics. However, it has been observed that the designs of some public building facades in Bali were produced without due consideration for the meaning and philosophy of these ornaments. Therefore, this research was conducted to examine and analyze the importance of the cultural value symbol expression associated with the peciren bebadungan in Bali using a qualitative exploration method. The findings showed the implementation of the style on several public buildings in Bali, specifically in Denpasar City and Badung Regency, in combination with contemporary designs. Some others also apply the style but with incomplete implementation and modification through a simpler and more minimalistic concept. This was observed to have eliminated the inherent meaning and cultural symbol value. Therefore, it is recommended that the government, architects, as well as the entire community, need to play a very important role in preserving the peciren bebadungan cultural value symbol expression.